Effects of Chinese word structure on object perception in Chinese–English bilinguals: Evidence from an ERP visual oddball paradigm. Issue 1 (3rd January 2021) - Pan, Xuan; Jared, Debra
Abstract: Lupyan's (2012) label-feedback hypothesis proposes that linguistic labels affect our conceptual and perceptual representations through top-down feedback. We investigated whether such representations in bilinguals are influenced by labels from both of their languages by examining the effect of Chinese word structure on picture perception in Chinese–English bilinguals. A visual-oddball task with ERP was used. Pictures of four birds were used as standards and deviants. The robin-ostrich pair shared a category cue in their Chinese names (like blackbird in English), and the pigeon-penguin pair did not. In Chinese–English bilinguals who were new to Canada, the visual mismatch negativity (vMMN) elicited by deviant stimuli was significantly larger for pairs without category cues than pairs with cues, but, in long-stay bilinguals and English monolinguals, the vMMN was similar for the two pairs. These results demonstrate that object perception is influenced by the labels in both of a bilingual's languages.